Penggunaan TIK Dan Internet Sebagai Media Belajar Untuk Meningkatkan Kinerja Guru - Siti Khayroiyah; Amanda Syahri Nasution (Universitas Muhammadiyah Sumatera Utara, 2018)
The rapid progress of technology is supporting all aspects of daily activities, offices and learning in the world of education. Technology can be used as a learning innovation. However, in fact there are still many teachers who have not been able to apply the use of technology so that it cannot be used as an innovation in learning. The lack of teacher ability in this case has an impact on the lack of teacher performance in the use of technology as a learning medium. To reduce and overcome this training was held to improve teacher performance. The activities were carried out in the school are the introduction and use of ICT and the Internet as learning media that can be used to support teaching and learning in the school. The activities aims to (1) form teacher working groups, (2) practice teachers to use ICT, (3) practice teachers to use the internet and (4) practice and guide teachers to use ICT and the internet as learning media. The activities were carried out in SD Medan Petisah sub-district which was attended by 13 teachers from 060847 State Elementary School and 11 teachers from 060848 State Elementary School.